2013
DOI: 10.1002/2013rs005157
|View full text |Cite
|
Sign up to set email alerts
|

Elevation angle‐of‐arrival determination for a standard and a modified superDARN HF radar layout

Abstract: [1] Calculations have been developed for the determination of elevation angle of arrival for a modified Super Dual Auroral Radar Network (SuperDARN) HF radar antenna layout consisting of dual auxiliary interferometer arrays: one behind and one in front of the main array. These calculations show that such a layout removes the 2 ambiguity or angle-of-arrival aliasing effect observed in existing SuperDARN HF radars. Ray tracing and simulation results are presented which show that there is significant potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…There was a distinct saturation effect in the observed elevation for moderate and high solar activity years. This can be explained by peculiarities of the antenna system such as (1) elevation angle aliasing effect at which the maximum measurable elevation is limited by 45° (Milan et al 1997;McDonald et al 2013;Ponomarenko et al 2015) and (2) partially by the narrow elevation radiation pattern (it affects the location of the power maximum that the procedure searches in each sounding session). However, the observed effective height on average agreed well with simulated one.…”
Section: F2mentioning
confidence: 99%
“…There was a distinct saturation effect in the observed elevation for moderate and high solar activity years. This can be explained by peculiarities of the antenna system such as (1) elevation angle aliasing effect at which the maximum measurable elevation is limited by 45° (Milan et al 1997;McDonald et al 2013;Ponomarenko et al 2015) and (2) partially by the narrow elevation radiation pattern (it affects the location of the power maximum that the procedure searches in each sounding session). However, the observed effective height on average agreed well with simulated one.…”
Section: F2mentioning
confidence: 99%
“…Geolocating the scattering volume depends on the ability to accurately estimate the HF propagation path to and from the volume (Greenwald et al, 2017). The SuperDARN radars are equipped with interferometers that make it possible to determine the elevation angle of arrival of the returning radio signals and, consequently, to estimate the most likely propagation modes and propagation path (André et al, 1998;Burrell et al, 2015;Chisham & Freeman, 2013;McDonald et al, 2013;Milan et al, 1997;Shepherd, 2017). Hence, using this information makes it possible to accurately estimate the geographic location of the scattering volume.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the phase angle in the SuperDARN interferometric measurements is reported between ±π while it actually can be different by multiples of 2π . SuperDARN radars report only the lowest possible elevations 2π , from Milan et al 1997;McDonald et al 2013;Ponomarenko et al 2015Ponomarenko et al , 2018. This ambiguity has not been addressed in the P2011 approach that we implemented in this study.…”
Section: Superdarn Methods Of F Region Peak Electron Density Estimatesmentioning
confidence: 99%
“…The P2011 technique assumes that the elevation angles can be measured for any angle between 0 • and 90 • . In reality, however, because the interferometer base exceeds the radar wavelength by a factor of three to five, the measured elevation angle has an uncertainty (e.g., Milan et al 1997;McDonald et al 2013;Ponomarenko et al 2015Ponomarenko et al , 2018 in that a single reported value of can correspond to several propagation paths in the ionosphere. This is because the phase angle in the SuperDARN interferometric measurements is reported between ±π while it actually can be different by multiples of 2π .…”
Section: Superdarn Methods Of F Region Peak Electron Density Estimatesmentioning
confidence: 99%